Analysis Of Competency Based Human Resource Development On CV. Digphotowork - Rani Amahika; Alifian Nugraha (Penerbit Jurnal Indonesia, 2024)
Human resources are an important element in the company, in order to develop company performance, of course, the company needs activities or programs that focus on improving the abilities of its employees. CV. Digphotowork is a business engaged in photography services managed by employees who are professionals in their fields. The purpose of this research is to find out competency-based human resource development at CV. Digphotowork and to find out changes in terms of employee performance after this competency-based human resource development. The research method carried out is descriptive qualitative, with data collection techniques by observation, interview, and documentation. Data analysis is done by reducing data, presenting data, drawing conclusions or verification, and checking data validity. The results of this study indicate that this competency-based human resource development program is carried out by providing training on photography, videography, and editing. At the same time, managerial aspects are also developed so as to produce a more optimal quality of employee performance.